2005
DOI: 10.1097/00008483-200511000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation is Associated With an Improvement in C-Reactive Protein Levels in Both Men and Women With Cardiovascular Disease

Abstract: Participation in CR was associated with a marked improvement of cardiac risk factors and appears to independently decrease the level of CRP regardless of gender, age, or presence of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 13 publications
5
29
0
Order By: Relevance
“…9 Similar results were found in the study by Caulin-Glaser and Attarbashi Moghadam. 10,11 In present study, we also found that serum hs-CRP levels decreased significantly following cardiac rehabilitation, as it has been reported previously. We found no study available evaluating the effects of exercise on salivary hs-CRP in patients with CAD.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…9 Similar results were found in the study by Caulin-Glaser and Attarbashi Moghadam. 10,11 In present study, we also found that serum hs-CRP levels decreased significantly following cardiac rehabilitation, as it has been reported previously. We found no study available evaluating the effects of exercise on salivary hs-CRP in patients with CAD.…”
supporting
confidence: 90%
“…However, our findings of nonsignificant association between hs-CRP and anthropometric measures of obesity is in agreement with previous results showing that exercise training could mitigate the hs-CRP levels independent of changes in body weight or body mass index. 2,[9][10][11] In the present study, serum hs-CRP levels were reduced by 36% after aerobic exercise training without any changes in central obesity parameters, indicating that other mechanisms leading to the anti-inflammatory effect of exercise.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…They found a significant reduction in CRP after the 3-month intervention in CAD patients with and without metabolic syndrome [296], in weight gainers and losers [295], and in patients with or without statin therapy [295]. This data was later confirmed by Caulin-Glaser et al [297], who reported a consistent reduction of CRP in patients who showed no improvement or an increase in triglycerides, body mass index, and weight. Others [289,290,298] also observed the statins and weight loss-independent effects of exercise on CRP and other markers of inflammation.…”
Section: Effects Of Regular Physical Exercise On Crp and Other Inflammentioning
confidence: 83%